Desain Pengisian Optimal Kendaraan Listrik Berdasarkan Kebutuhan Daya Grid dan Kondisi Grid pada Stasiun Pengisian Kendaraan Listrik Menggunakan Kontroler Logika Fuzzy - Onang Surya Nugroho; Dimas Anton Asfani; Daniar Fahmi (Direktorat Riset dan Pengabdian Masyarakat (DRPM), ITS, 2016)
Electric vehicles has become one of alternatives in addressing energy crisis in the field of transportation. Increasing the number of electric vehicles that are not accompanied by a proper charging station management would give negative impact either to the distribution system on the network such as voltage fluctuation, voltage drop, voltage stress, lack of continuity of the power system, and even cause the blackout. Energy management design is needed for electric vehicles charging stations to obtain optimal power flow model between charging station and grid. This research will be designed an analysis and design of optimal charging by considering estimated power flow between charging station with the grid and load conditions on the grid (off-peak / peak) using fuzzy logic controller. This charging management uses the concept vehicle to vehicle (V2V), vehicle to grid (V2G), and the grid to vehicle (G2V) which adjust by charging index and charging rate results from rule fuzzy scoring result. The simulation results show that the fuzzy-based system can flatten the load curve peak of electric vehicle, reducing the impact of peak load to the grid, and can provide cost advantages in the form of cost saving.